(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article examines the impact of chronic stress on the morphology of the hippocampus. The study compares the hippocampal structure and developmental dynamics of laboratory rat offspring born to stressed mothers with those in a control group. The results indicate that offspring exposed to stress exhibit a reduction in hippocampal neurocytes, vacuolization of the cytoplasm, changes in nuclear and cytoplasmic size, as well as neurocyte lysis. Additionally, the body weight of stressed rat offspring was found to be lower than that of the control group. The obtained data suggest that stress may have a negative impact on hippocampal structure.